The Mechanism of Carbonate Alkalinity Exposure on Juvenile Exopalaemon carinicauda With the Transcriptome and MicroRNA Analysis - Shi, Kunpeng; Li, Mingdong; Qin, Zhen; Wang, Jiajia; Liu, Ping; Li, Jian; Li, Jitao (Frontiers in Marine Science, 2022)
Saline-alkali water is distributed all over the world and affects the development of fisheries. The ridge tail white prawn Exopalaemon carinicauda is an economically important shrimp in China, which has excellent environmental tolerance. However, due to its complex genetic structure, there have been few studies on its alkalinity-adaptation mechanisms. In order to explore the molecular mechanisms of E. carinicauda in adapting to the alkaline water, mRNA and miRNA transcriptomes from the gills of E. carinicauda were determined. The results showed that after alkalinity stress, the structures of the gill and hepatopancreas were disorganized; however, E. carinicauda could still maintain vital signs. Transcriptome results showed that ATP binding protein and carbonic anhydrase played an important role in alkalinity-adaptation. At the same time, a large number of immune-related genes were up-regulated, which protect E. carinicauda from bacterial infection. MiRNAs also played an important role in alkalinity-adaptation. A total of 24 miRNAs were identified as differentially expressed after alkalinity stress, and up-regulated miRNAs might active the GnRH signaling pathway and accelerate the synthesis and secretion of aldosterone, which might maintain the balance of osmotic pressure in E. carinicauda to adapt to alkaline environment. These results provide a better understanding of the alkalinity-adaptation mechanism of economic aquatic animals and provide theoretical basis for breeding in the future.